Implementation of the European Landscape Convention in Hungary - short review - Kincses, Krisztina (4D Journal of Landscape Architecture and Garden Art, 2019)
The European Landscape Convention of the Council of Europe was adopted by the Committee of Ministers of the Council of Europe on 19 July 2000 and opened for signature to its Member States in Florence on 20 October 2000. Hungary immediately began the process of preparing for its implementation. The European Landscape Convention finally came into force on 1 February 2008 in Hungary.
Keywords: Landscape; Convention; European